2015
DOI: 10.1080/15299732.2015.1126777
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and exposure to trauma reminders after a terrorist attack

Abstract: The aims of this study were twofold: (a) to systematically describe the type and frequency of trauma reminders reported after a terrorist attack and (b) to examine whether posttraumatic stress disorder (PTSD) is associated with frequency of exposure to trauma reminders. A total of 285 survivors (M age = 22.2, SD = 4.3, 53% males) of the 2011 massacre on Utøya Island, Norway, were interviewed face to face 14-15 months after the terror. Participants were asked how often they had experienced a range of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…This study examined post-traumatic stress symptoms and functional impairment among Israeli foster care social workers and the type of help they needed and received following armed conflict. Similar to previous studies both among children (Slone, Lavi, Ozer, & Pollak, 2017) and adults (Glad, Jensen, Hafstad, & Dyb, 2016), and in support of Hypothesis 1, we found that exposure to the armed conflict was moderately associated with post-traumatic stress symptoms and functional impairment. Nonetheless, only 11% felt functional impairment with regard to their treatment of the foster family.…”
Section: Discussionsupporting
confidence: 91%
“…This study examined post-traumatic stress symptoms and functional impairment among Israeli foster care social workers and the type of help they needed and received following armed conflict. Similar to previous studies both among children (Slone, Lavi, Ozer, & Pollak, 2017) and adults (Glad, Jensen, Hafstad, & Dyb, 2016), and in support of Hypothesis 1, we found that exposure to the armed conflict was moderately associated with post-traumatic stress symptoms and functional impairment. Nonetheless, only 11% felt functional impairment with regard to their treatment of the foster family.…”
Section: Discussionsupporting
confidence: 91%
“…Increased levels of distress can occur when trauma reminders of an event lead the victim to re-experiences the traumatic event. Trauma reminders are cues that mirror or resemble events experienced during the traumatic event and consequently cause similar reactions of the event itself (Glad, Jensen, Hafstad, & Dyb, 2016). Two hundred eighty five survivors of the Utoya Island attack were interviewed to identify trauma reminders and to evaluate whether experiencing trauma reminders correlated to levels of PTSD.…”
Section: The First Policy To Evaluate Is the Communication Protocols mentioning
confidence: 99%
“…From this interview, seven general types of trauma reminders for the Utoya attack were identified. The seven types of trauma reminders were: auditory, situational, emotional, visual, bodily reactions, olfactory, and tactile (Glad, et al, 2016).…”
Section: The First Policy To Evaluate Is the Communication Protocols mentioning
confidence: 99%
See 2 more Smart Citations